Implementing Best Practices for Nurses in Detecting and Reporting Adverse Drug Reactions in a Tertiary Hospital in Tabriz, Iran: A Mixed‐Method Study - Neda Kabiri; Sakineh Hajebrahimi; Parvin Rahmani; Fatemeh Molaei Tavani; Seied Hadi Saghaleini; Saiedeh Razi Soofiyani; Amin Talebpour (Health Science Reports)
ABSTRACT Background and Aims According to the World Health Organization (WHO), an Adverse Drug Reaction (ADR) is defined as “a response to a drug which is noxious and unintended, and which occurs at doses normally used in humans for the prophylaxis, diagnosis, or therapy of disease, or for the modification of physiological function.” The aim of this research was to evaluate the current practice and implement the best practices for detecting and reporting ADR in a tertiary hospital in Tabriz, Iran. Methods We used a mixed‐methods sequential explanatory design in the current study. The research was conceptually informed by the Joanna Briggs Institute model of Evidence‐Based Healthcare (JBI EBHC). A three‐phase implementation process, outlined by this model, was used in this study. The first and third phases comprised the quantitaive phase of the study, in which we evaluated the current practice and conducted a final evaluation to measure changes in compliance with the best practice. The qualitative phase, the second phase of the JBI EBHC model, was conducted to identify barriers and develop implementation strategies. There were seven evidence‐based audit criteria for evaluating the practice, with a sample size of 23 nurses for the quantitative phase and 10 participants for the qualitative phase. Results The quantitative findings revealed an improvement in compliance rates for all criteria following the follow‐up audit. From the qualitative analysis, four themes of barriers were identified: time and workload, lack of a proper reporting system for ADR, lack of belief and readiness for change among nurses, and lack of awareness about the importance of documenting ADR. Conclusion The results of this implementation study demonstrated enhanced ADR reporting. It can be inferred that implementing educational strategies, such as holding conferences, informal meetings, workshops, and educational pamphlets, can facilitate the implementation of evidence into practice. Implications for Nurses Findings will help nurses across sectors of primary, secondary, and tertiary care use the implemented strategies to improve the quality of care and reduce ADR.